Book Processing System (bps) for bookstore / Chang Chin Hung - Chang, Chin Hung (2002)
The objective of this project is to develop a computerized Book Processing System (BPS) for the bookstore which still runs their operation manually. The target is the bookstore that main activity is renting novel, comic, and etc besides selling newspaper or magazine. BPS is comprised from the different modules such as circulation module (rent, return, sell and fine for missing or overdue), book master, customer master (member or non-member), report generation and maintenance module. The main function of this BPS is to do the transaction between staff and customer while customer desire to rent, return, buy, reserved or has been fined for missing or overdue. Secondly is to handle membership fee and maintain customer information in database. Besides that, the system is used to store book information and other information to facilitate the administrator to maintain the business. In this case, report generation is one of the functions for BPS. The others function like search, help, promotion, backup database and change password will be provided also. For the methodology, traditional Waterfall model approach is selected for the development BPS. This method is adopted because ease of implementing. In addition, it supports rapid application and reduces the risk involved. Besides, the BPS is developed using Visual Basic 6.0 and Microsoft Access 2000 on the Window 2000 platform. Microsoft Visio is used to draw the flow chart and additional software will be used to create the bar code of the book too.